A Comparative Study of Interaction of Tetracycline with Several Proteins Using Time Resolved Anisotropy, Phosphorescence, Docking and FRET - Mukherjee, Manini; Saha Sardar, Pinki; Ghorai, Shyamal Kr.; Samanta, Swarna Kamal; Roy, Atanu Singha; Dasgupta, Swagata; Ghosh, Sanjib (PLOS ONE, 2013)
A comparative study of the interaction of an antibiotic Tetracycline hydrochloride (TC) with two albumins, Human serum albumin (HSA) and Bovine serum albumin (BSA) along with Escherichia Coli Alkaline Phosphatase (AP) has been presented exploiting the enhanced emission and anisotropy of the bound drug. The association constant at 298 K is found to be two orders of magnitude lower in BSA/HSA compared to that in AP with number of binding site being one in each case. Fluorescence resonance energy transfer (FRET) and molecular docking studies have been employed for the systems containing HSA and BSA to find out the particular tryptophan (Trp) residue and the other residues in the proteins involved in the binding process. Rotational correlation time (θc) of the bound TC obtained from time resolved anisotropy of TC in all the protein-TC complexes has been compared to understand the binding mechanism. Low temperature (77 K) phosphorescence (LTP) spectra of Trp residues in the free proteins (HSA/BSA) and in the complexes of HSA/BSA have been used to specify the role of Trp residues in FRET and in the binding process. The results have been compared with those obtained for the complex of AP with TC. The photophysical behaviour (viz., emission maximum, quantum yield, lifetime and θc) of TC in various protic and aprotic polar solvents has been determined to address the nature of the microenvironment of TC in the protein-drug complexes.